2016
DOI: 10.3329/jujbs.v5i1.29742
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological pollutants in air and antibiotic resistance profile of some bacterial isolates

Abstract: Microbiological quality assessment is one of the most important investigations to determine the pollution of indoor and outdoor air. To evaluate the microbial load in air, samples were collected from 3 different outdoor and 3 different indoor sites within Jahangirnagar University campus. In outdoor air, bacterial and fungal counts varied from 117 -7284 CFU/m 3 and 88 -5287 CFU/m 3 , respectively. On the other hand, in indoor air bacterial and fungal counts varied from 440 -6226 CFU/m 3 and 88 -5874 CFU/m 3 , r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Their high susceptibility perhaps could be due to the fact that these drugs mostly are administered via the parenteral routes which will limit their misuse and/or abuse which had been reported to account for the upsurge in the incidence and preponderance of resistance amongst antibiotics. This conforms to the report of other workers such as those of Ngwai et al [24], Isibor and Ekundayo [29], Makut et al [6] and Kabir et al [23]. There is established evidence that for most bacteria, increased usage of a particular drug correspond with increased incidence and prevalence of bacterial resistance [30]; perhaps this explains the high resistant of the bacterial isolates against the following readily used antibiotics, viz; Amoxicillin and Septrin.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Their high susceptibility perhaps could be due to the fact that these drugs mostly are administered via the parenteral routes which will limit their misuse and/or abuse which had been reported to account for the upsurge in the incidence and preponderance of resistance amongst antibiotics. This conforms to the report of other workers such as those of Ngwai et al [24], Isibor and Ekundayo [29], Makut et al [6] and Kabir et al [23]. There is established evidence that for most bacteria, increased usage of a particular drug correspond with increased incidence and prevalence of bacterial resistance [30]; perhaps this explains the high resistant of the bacterial isolates against the following readily used antibiotics, viz; Amoxicillin and Septrin.…”
Section: Discussionsupporting
confidence: 89%
“…However, several workers have reported similar microorganisms within air environment of both indoor and outdoor air [10,6,23,16]. Pseudomonas aeruginosa, Bacillus spp., Micrococcus spp.…”
Section: Discussionmentioning
confidence: 97%
“…However, this study aimed to enumerate the prevalence of the microorganisms present in the air of Dhaka city to get an idea of the kind of pathogenic bacteria present in such an extremely polluted area. Every day, 14 m 3 of air is inhaled by a person [4] [5]. If there are numerous pathogenic microbes in the air that people inhale, it could be health hazardous for them.…”
Section: Introductionmentioning
confidence: 99%
“…With each human being inhaling 14 m 3 of air per day on the average (Kabir et al, 2016), the potential impact air quality has on the quality of human life cannot be overemphasized. The microbial analysis of indoor air quality carried out in this study revealed a count range of 200 -11850 CFU/m 3 and these were generally (12/14) above the recommended acceptable standards.…”
Section: Literature Review/summary Of Literaturementioning
confidence: 99%
“…A World Health document outlining the WHO guidelines for indoor air quality, describes healthy indoor air as a fundamental human right. This is particularly important considering that a significant number of people have been reported to spend the majority of their time (between 80% and 90%) indoors (Hospodsky et al, 2012;Hayleeyesus and Manaye, 2014 (Nevalainen and Morawska, 2009;Borrego et al, 2012;Naruka and Gaur, 2013;Kabir et al, 2016).…”
Section: Introductionmentioning
confidence: 99%